Hak Memilih Pasangan Bagi Wali Nikah Di Desa Banyubang Kecamatan Solokuro Kabupaten Lamongan Perspektif Gender - Abd. Rouf; Mufidah Cholil; Suwandi Suwandi (IAI Darussalam, 2021)
This study intends to review whether the right to choose a spouse for the guardian of marriage is still relevant to be applied in this era. This research is a field study that uses a social approach through the process of observation, interview, and document study. The populations and samples that have been obtained are then analyzed using deductive and inductive methods. The results of this study are the right of ijbar (the right to choose a partner for marriage guardians) is no longer relevant to be applied, this is because in Indonesia there is already a marriage law in which there is a clause that marriage must be carried out based on the approval of the two prospective brides, while on the other hand the unilateral coercion is very contrary to the concept of gender equality and justice and is a form of accumulation of gender discrimination. Forced marriage is heavily fraught with marginalization, subordination, stereotypes, violence and will increase the potential for the workload